The Influence of Cooperation and Skills on Extracurricular Volleyball Performance at High School - Maharani Masyita; Rusli Rusli; M. Adam Mappaompo (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Optimal performance in school sports relies on individual capabilities and team dynamics, yet the empirical balance between technical skills and teamwork remains unclear. This study examines the independent and simultaneous effects of volleyball technical skills and teamwork on extracurricular performance at High School 2 Maros. Using a quantitative approach with an explanatory and correlational design, this study applied total sampling to all program members (N = 30). Data gathered via Likert-scale questionnaires, observations, and documentation were analyzed using descriptive statistics, assumption tests, Spearman correlation, and multiple linear regressions in SPSS. The results indicate that technical skills (X1) have a positive and significant effect on performance (Y), with a regression coefficient of 0.873 (t = 3.554; p = 0.001 < 0.05) and a moderate correlation (r = 0.462). Conversely, teamwork (X2) shows a positive but non-significant independent effect (coefficient = 0.153; p = 0.578 > 0.05; r = 0.191). However, simultaneously, both variables exert a significant joint effect on performance (F = 6.942; p = 0.004 < 0.05). This study contributes to sports pedagogy by demonstrating that extracurricular volleyball success is predominantly driven by individual technical skill mastery. It provides actionable insights for coaches to prioritize rigorous technical training while maintaining teamwork as a complementary predictive factor to optimize student athletic outcomes.